2013
DOI: 10.4103/0972-124x.115663
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of efficacy of autologous platelet-rich fibrin with demineralized-freeze dried bone allograft in the treatment of periodontal intrabony defects

Abstract: Background:Platelet-rich fibrin (PRF), an intimate assembly of cytokines, glycan chains, and structural glycoproteins enmeshed within a slowly polymerized fibrin network, has the potential to accelerate soft and hard tissue healing. The purpose of the study was to clinically evaluate and compare the efficacy of autologous PRF combined with demineralized freeze-dried bone allograft (DFDBA) to DFDBA alone in the treatment of periodontal intrabony defects.Materials and Methods:In a split mouth study design, 10 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 15 publications
2
21
0
Order By: Relevance
“…Periodontal regeneration aims to regenerate bone, cementum and periodontal ligament lost due to the disease process and the reasoning behind the techniques chosen in this case is described below . The use of DFDBA faciliates periodontal regeneration due to its osteoinductive and osteoconductive properties.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Periodontal regeneration aims to regenerate bone, cementum and periodontal ligament lost due to the disease process and the reasoning behind the techniques chosen in this case is described below . The use of DFDBA faciliates periodontal regeneration due to its osteoinductive and osteoconductive properties.…”
Section: Discussionmentioning
confidence: 99%
“…These growth factors are progressively released over a period of time as the fibrin network disintegrates . Studies have shown that PRF with DFDBA results in probing pocket depth reduction and gain in clinical attachment level when compared to DFDBA alone . This was attributed to the haemostatic effect of PRF and also its effects as a biologic connector that holds the graft materials together .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Five RCTs addressing the prospective application of L-PRF in the treatment of Periodontal IBD were found. The identified studies allowed for the following comparisons: (a) L-PRF/Open flap surgery vs. Open flap surgery [10][11][12], (b) L-PRF/Bio-Oss® constructs (Bio-Oss®, Geistlich Pharma North America, Inc.) vs. L-PRF [13] and (c) L-PRF/DFDBA constructs vs. DFDBA (Demineralized Freeze-Dried Bone Allograft) [14]. All patients included in those studies were periodontally stable and systemically healthy individuals who presented: similar bilateral IBD of at least 5 mm probing depth, located in vital asymptomatic teeth with no furcation involvement.…”
Section: L-prf In the Treatment Of Periodontal Intrabony Defects (Ibds)mentioning
confidence: 99%
“…The presented PD reduction and CAL gain values were superior to previously-reported values in meta-analysis performed for open flap surgery [9], suggesting the additional benefits of L-PRF over the conventional approach. Treatment with L-PRF/particulate bone-graft substitutes (Bio-Oss® [13] and DFDBA [14]) provided additional statistically-significant benefits, in terms of PD reduction, CAL gain and bone defect fill vs. graft substitutes, after 6 months. Nonetheless, the absence of "simultaneously-run" L-PRF-alone control renders it difficult to distinguish between the effects of L-PRF and other potential variables in the study.…”
Section: Gingival Margin Stability [(Gms) Less Post-treatment Gingivamentioning
confidence: 99%